The Effects of Asphodel (Asphodelus aestivus Brot.) Rhizome Extract Administration in the Treatment of Thermally Induced Wound in Rats - Arihan, Okan; Akgul, Omer; Oto, Gokhan; Yildirim, Serkan; Eroglu, Huseyin; Bora, Gulhan (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Burn wound is an important health problem worldwide. Serious outcomes related with burn occur and treatments focus on healing of the wounded area with dermal preparations containing chemicals avoiding growth of pathogenic organisms. Plants are important sources for both modern pharmacy to find new molecules used in modern medication as well as in traditional medicinal practices. Many plants are used for treatment of burn wounds. Asphodel (Asphodelus aestivus Brot.) is a naturally found plant in the Mediterranean flora. It is also used in traditional medicinal practices in Turkey. Aim: In this study it was aimed to test wound healing effect of Asphodel. Materials and Methods: An ointment prepared with a 5% methanolic extract of Asphodel was used. 4 groups were formed as control, wound, wound+asphodel and wound+standard drug (oxytetracyclin hydrochloride) (n=8 in each group). Burn wound was established with a thermal induction. Biochemical, microbiological and histopathological evaluations were performed. Results: Biochemical results (Alt, Ast, Glucose, Ldh) obtained from blood samples showed no adverse effect of this administration. Microbiological results showed a protective effect of Asphodel similar with standard drug. Histopathological evaluation also presented an ameliorating effect as standard drug. Conclusion: Results of this study states that traditional use of this plant for the treatment of burn/wound/ulcer in traditional medicine applications is valid.
Keywords: Burn; Asphodel; Asphodelus; Rat; Skin; Ethnopharmacology